MUHAMMAD HASHIM THATTWI AND HIS EDUCATIONAL EFFORTS - SALIH, KHALIL AHMED; YAQOOB, SARDAR AHMED; AHMED, SUMYYAH SARDAR (Journal of Islamic Sciences, 2019)
This article of mine has been written on such personality who is famous and his educational efforts are featured in different educational fields. This personality with all his pelvis and interest has worked in ballad, compilation, fatwa, Fiqah and literature. Above all, he also got across languages other than his mother tongue. Even he got across Arabic language as well. And though he is not that much famous in Arabic countries but his personality is discussed in all academic circles in Pakistan especially in the Sindh province. This is the reason I have chosen this personality for this article so that I can highlight his research overview from different aspects. Here this is also noteworthy that in this article I have debated upon his personality, and in this case I have mentioned details and statements about him, and the services he did are also discussed in detail with complete explanation under research title. And the teachers from whom he got education whether they belong to Pakistan or foreign countries, their brief introduction is also discussed. This article of mine contains one trial, seven topics and an end. And in the end of the article, important results are also registered. And this personality Muhammad Hashim Thattwi travelled different parts of the world in order to get education which I have mentioned in this article. And his position was very high in all the academic circles. The evidence of his highness is that his colleagues and other scholars have appreciated his work. This is the clear evidence that Muhammad Hashim Thattwi was delusional scientific character. And in the end of the article I have mentioned his date of death and the place where he is buried.